Study on vibration monitoring and anti-vibration of overhead transmission line - Yin Weihua (De Gruyter, 2021)
Numerous forms of dampers are used to eliminate the vibrations in transmission lines. In the contemporaneous editorial, a survey has been done on vibrations monitoring and anti-vibration of overhead transmission line of transmission lines having multiple dampers for dissimilar cable sizes. To investigate the outcome of the position of dampers on extreme strains created in the line. A comprehensive survey of the extreme strains created is also made for several wind power input conventions. A finite element technique is used to measure the frequency and manner figures of the cable with and without a damper. The response of the bare conductor, loaded conductor, the conductor for various dampers’ location is also studied. Spoilers and torsional dampers are maximum actual in diminishing electrode galloping, while dampers are quite the utmost effectual plans for aeolian shakings and spiral dampers are admirable for identical lesser width of electrodes.